Evaluasi Kebijakan Bongkar Muat Barang untuk Mencegah Terjadinya Demmurage pada Perusahaan Keagenan Kapal di Wilayah Pelabuhan Tanjung Emas Semarang - Anggoro, Retno; Padilah, Haris; Suprapti, Fitri (Majalah Ilmiah Gema Maritim, 2024)
Demurrage or the cost of more time loading and unloading goods at the port is an undesirable additional cost for ship agency companies. This study aims to evaluate the policies and procedures for loading and unloading goods at three ship agency companies, namely PT Karisma Indah Lestari and PT Dasa Karindo Utama in the Tanjung Emas Port area of Semarang to prevent demurrage costs. This study used a qualitative approach with purposive sampling techniques. Data collection was carried out through in-depth interviews, direct observation, documentation studies, and literature studies related to loading and unloading activities. The results showed that the main causes of demurrage were document delays, container turnover, additional cargo volumes, to complicated administration. The policy evaluation indicated the need for improvement of standard operating procedures, coordination between stakeholders, and internal supervision to ensure the loading and unloading process was effective and timely according to the agreement. The recommendations given were a revision of stevedoring policies and procedures that are more measurable, improved coordination across sectors, additional supporting facilities and infrastructure, and strengthened operational supervision in the field.